High-resolution 3D tractography of fibrous tissue based on polarization-sensitive optical coherence tomography - Yao, Gang (Exp Biol Med (Maywood), 2019)
Fibrous tissues play important roles in many parts of the body. Their highly organized directional structure is essential in achieving their normal biomechanical and physiological functions. Disruption of the typical fiber organization in these tissues is often linked to pathological changes and disease progression. Tractography is a specialized imaging method that can reveal the detailed fiber architecture. Here, we review recent developments in high-resolution optical tractography using Jones matrix polarization-sensitive optical coherence tomography. We also illustrate the use of this new tractography technology for visualizing depth-resolved, three-dimensional fibrous structures and quantifying tissue damages in several major fibrous tissues. IMPACT STATEMENT: Organized fiber structure plays an essential role in realizing normal biological functions in fibrous tissues. A thorough understanding of the structure–function relationship in these tissues is crucial for developing effective technology to diagnose and treat diseases. Tractography imaging is an effective tool in visualizing and quantifying fiber architecture in fibrous tissues. This review describes a recently developed tractography technology that has shown great promise for fast image of 3D fiber organization with microscopic details.